Sincerity of Main Character in The Maze Runner Movie Directed By Wes Bell - Wiruma Titian Adi; Leony Rubi Yanti (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2022)
This research aims to observe the characteristic of sincerity shown in the main character and discover the effect of the main character’s sincerity. Using a qualitative method, the characteristic of the main character is analyzed based on the theory of a. characteristic of sincerity b. the effect of the main character’s sincerity. As a result of analysis, the writers found that: 1. The characteristics of sincerity shown in the main character along the story 2. The effects also objective truth along the story 3. The primary moral messages implied in the movie are about improving a better person, making a judgment, and the principles avowed by society and the sincerity of its citizens.